Health-risk assessment of Portuguese man-of-war (Physalia physalis) envenomations on urban beaches in Sao Luis city, in the state of Maranhao, Brazil - Silva Cavalcante, Mayana Mendes E.; Ribeiro Rodrigues, Zulimar Marita; Hauser-Davis, Rachel Ann; Siciliano, Salvatore; Haddad Junior, Vidal [UNESP]; Silva Nunes, Jorge Luiz (Soc Brasileira Medicina Tropical, 2020)
Introduction: The Portuguese man-of-war (Physalia physalis) is a cosmopolitan species, with a widespread distribution and responsible for a great number of injuries caused by cnidarians worldwide, including Brazil. Geoprocessing technology, however, has never been used to assess the spatial distribution of these animals on beaches. The aim of this study was to carry out a health risk assessment of Portuguese man-of-war (P. physalis) envenomations on the Sao Marcos and Calhau beaches in Sao Luis city. in the state of Maranhao, Brazil. Methods: This is a descriptive and quantitative study concerning primary data on the occurrence of the Portuguese man-of-war (P physalis) and human envenomations in the studied places, conducted over a two-year period in Sao Luis, Maranhao, northeastern Brazil. Results: Envenomations mainly occurred on beaches presenting high density of P physalis during the dry period. Vinegar has been incorporated as a first aid, according to recommendations set by the Brazilian Ministry of Health. Conclusions: In order to improve prevention and control actions of human envenomation, risk areas for this type of envenomation should be clearly indicated as alert areas. Inclusion of the geographical location of the envenomation in the Notification/Investigation SINAN Form was suggested for allowing the continuity of studies involving this public health issue.
Keywords: Physalia physalis; Geographic mapping; Venomous animals; Injury prevention; Public health